The role of micro-enterprises in post-growth urban transitions: An inquiry in Athens and Barcelona - Koukoufikis, Giorgos (The Greek Review of Social Research, 2020)
This paper brings forward empirical research assessing the potential influence of micro-enterprises to urban post-growth systemic transformations. Athens and Barcelona used as urban laboratories to document the factors (discursive, structural, and institutional) that influenced micro-entrepreneurial adaptation strategies to the post-2008 crisis and thus to discover to what extent the altered discourses and practices of this agency exhibit potential to stimulate wider socio-economic transformations. The field engagement targeted ‘‘conventional’’ micro-enterprises, operating at street-level in traditional market sectors and micro-enterprises operating in the social and solidarity economy. The results indicate that the crisis indeed provided context for path-shaping processes towards alternative urban economic realities in which this particular agency has an important role to play. However, for a transformative process to capitalize, further empowerment, institutional framing and material support needed along with the activation of other types of collective and individual agencies.